Transport properties of membrane vesicles from Acholeplasma laidlawii. I. Isolation and general characteristics - Fedotov, N S; Panchenko, L F; Logachev, A P; Bekkouzhin, A G; Tarshis, M A (Folia microbiologica, 1975)
A new procedure for the isolation of membrane vesicles from Acholeplasma laidlawii cells is described. The membrane vesicles are completely free from contaminations of whole cells and cell debris and represent a homogeneous fraction as shown by electron microscopy, Ficoll density-gradient centrifugation, and titration on agar plate. Absence of cytoplasmic contaminations was confirmed by double-labelling of membranes with 3H-oleic acid and 14C-uridine, as well as by distribution of specific marker enzymes of membranes and cytoplasm. On the basis of light-scattering and electron microscopy, the vesicular nature of these membranes was established. The vesicles had the same orientation as intact cells (absence on membrane vesicles of ATPase and NADH dehydrogenase activities, localized in the inner surface of membrane). The respiratory activity of the membrane vesicles was low and was not stimulated by exogenous substrates, the respiratory chain of the vesicles being reduced and terminated by flavoproteins. The ability of membrane vesicles to take up carbohydrates was shown.
Keywords: buněčná membrána; metabolismus sacharidů; Acholeplasma laidlawii; Glucose; glukosa; Adenosine Triphosphatases; Cell Fractionation; Cell Membrane; NADH, NADPH oxidoreduktasy; NADH, NADPH Oxidoreductases; frakcionace buněk; Oxygen Consumption; Glucokinase; glukokinasa; adenosintrifosfatasy; spotřeba kyslíku; Carbohydrate Metabolism